Online Processing of Novel Noun–Noun Compounds: Eye Movement Evidence. Issue 1 (January 2014) - Cohen, Andrew L.; Staub, Adrian
Three eye-tracking experiments investigated online processing of novel noun–noun compounds. The experiments compared processing of compounds that are difficult to interpret in isolation (e.g., dictionary treatment ) and more easily interpretable adjective–noun and noun–noun sequences (e.g., rough treatment and torture treatment ). In all three experiments, first-pass reading time was longer on the head noun ( treatment ) when it occurred in a difficult compound. Further, a preceding sentence that provided a potential interpretation of the critical compound reduced processing difficulty, but this modulation by context occurred in later eye movement measures, or downstream of the compound itself. These results are interpreted in relation to the eye movement literature on the processing of implausibility, which demonstrates a similar pattern in which the disruption in early eye movement measures is not alleviated by context, but context does have a later effect. The results also suggest that the interpretation of noun–noun compounds in context does initially depend on the availability of an out-of-context interpretation.